Power corrections to the production of a color-singlet final state in hadron collisions in the N-jettiness slicing scheme at NLO QCD - Prem Agarwal; Kirill Melnikov; Ivan Pedron; Philip Pfohl (Journal of High Energy Physics)
Abstract We compute next-to-leading power corrections in the zero-jettiness variable for the production of colorless final states at hadron colliders at next-to-leading order in QCD. To assess if the process-independence of leading power contributions can be extended, we attempt to construct generic expansions of phase spaces and matrix elements squared through next-to-leading power in the zero-jettiness. We highlight challenges associated with the collinear limit, where universality no longer holds at the subleading power, making the result process-dependent. We show that quantities that need to be calculated in the collinear limit can be obtained using Berends-Giele currents, enabling computation of power corrections to high-multiplicity final states. As a concrete example, we apply our method to compute power corrections in the zero-jettiness for lepton pair as well as multi-photon production in q q ¯ $$ q\overline{q} $$ collisions.